Rezim tanpa Rezim: Kepenataan dan Wacana Komunisme di Ranah Perbukuan Indonesia Kontemporer - Geger Riyanto (Human Narratives, 2019)
During the course of the New Order in Indonesia, communism and Indonesian Communist Party (PKI) as its manifestation was constructed as the nemesis of the state and even the whole nation. Communism became a taboo that everyone has to avoid or condemn. With the fall of the New Order, a lot of historical discourses about communism in Indonesia were produced to contend the official historiography. Formal discrimination through several laws and regulations against ex-PKI or allegedly communists was also stripped by the new government. However, the taboo and abjection itself is not entirely died out. In post-Reformasi Indonesia, the mechanism of rejection and condemnation to the communism has been working through many social processes. One of them is the censorship towards ‘leftist publications’ and persecutions towards public forums discussing ‘leftist discourses’, usually orchestrated by non-state actors, particularly civil or mass organizations. This article, using ethnography as its method and Foucauldian analysis of governmentality as theoretical framework, aims to discuss how such censorships and persecutions occur as a symptom of the ongoing abjection towards communism in Indonesia.